Investigating North American grassland biogeography throughout the Holocene - Commerford, Julie L. (Kansas State University, 2016)
Throughout the Holocene, North American grassland vegetation has shifted in composition and spatial extent. However, it has been difficult to characterize these changes because the drivers—particularly climate, fire, topography, or grazing from large herbivores—operate at different spatial and temporal scales. Long-term archives such as lacustrine sediment cores, and the proxy records they contain, can help illustrate vegetation changes on relevant timescales. Yet, accurate interpretations of grassland vegetation composition from pollen (a common proxy used to infer vegetation of the past) remain limited by the number of calibrations of pollen and the drivers of vegetation change in modern conditions. This research addresses those gaps by evaluating grassland vegetation at different spatial and temporal scales in the context of modern and historical drivers. First, I reconstruct vegetation composition and diversity, fire activity, and erosion activity at a sub-regional scale over the last 9,300 years by analyzing pollen, charcoal, and magnetic data from a sediment core from a grassland lake in southern Minnesota. Second, I quantify the relationships between modern grassland pollen and fire, grazing, and topography at a fine spatial and temporal resolution, using pollen samples collected annually from traps at Konza Prairie Biological Station in the Flint Hills of Kansas. Finally, I synthesize modern pollen assemblages across the Great Plains to create a transfer function that quantitatively links precipitation and temperature with pollen. I apply this function to pollen data from the past to interpret the climate history of three sites across the Great Plains, including the aforementioned site in southern Minnesota. The results from this research suggest that grassland vegetation diversity remained relatively resilient to the climatic fluctuations of the Holocene, including the driest time at 5,000 yr BP. In addition, this work facilitates more informed interpretations of fossil pollen by effectively calibrating modern grassland pollen assemblages with their abiotic and biotic drivers.
Keywords: Grasslands; Paleoecology; Great Plains; Pollen; Climate; Environmental reconstruction